2022
DOI: 10.1038/s41598-022-24473-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of subclinical depression on moral judgment dilemmas: a process dissociation approach

Abstract: Dual-process theory of moral judgment indicates that moral decision-making is guided by emotional or cognitive processing, competing with each other. While emotional processing overwhelms cognitive processing, individuals preferentially make deontological judgments. Further, while cognitive processing dominates emotional processing, individuals preferentially make utilitarian judgments. This theory predicts that individuals with subclinical depression associated with emotion regulation deficits may deliver mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…One common theme regards the deontological-utilitarian response differences mentioned above, studied from different approaches. One study examined whether people tend to trust deontological decision makers more than utilitarians 1 , another looked at the persuasive effect of deontological and utilitarian messages 2 , and yet another examined the way depression affected utilitarian and deontological aspects of moral decisions 3 . Like other works in this Collection, these include experimental designs that relied on vignettes, describing such moral dilemmas as the footbridge problem.…”
Section: Common Themes In the Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…One common theme regards the deontological-utilitarian response differences mentioned above, studied from different approaches. One study examined whether people tend to trust deontological decision makers more than utilitarians 1 , another looked at the persuasive effect of deontological and utilitarian messages 2 , and yet another examined the way depression affected utilitarian and deontological aspects of moral decisions 3 . Like other works in this Collection, these include experimental designs that relied on vignettes, describing such moral dilemmas as the footbridge problem.…”
Section: Common Themes In the Collectionmentioning
confidence: 99%
“…Others examined the effects of individual traits and emotions on moral decisions. Yin et al 3 examined the levels of emotional and cognitive processes of depression on moral judgement. Du et al 11 demonstrated mindfulness training could prevent moral preference decline over time without changing emotional regulation strategies.…”
Section: Common Themes In the Collectionmentioning
confidence: 99%
“…Second, we seek to explore whether personality traits previously implicated in lenient offence-related judgements (e.g., psychopathy) will also map onto infant homicide cases, and whether this relationship might be further moderated by the sex of the perpetrator. Variables likely to impact such outcomes, namely age, mental health stigma, mental wellbeing, and beliefs about gender roles will be controlled for (see Fido et al, 2022;Maroño & Bartels, 2020;Yin et al, 2022). Third, we explored participants' narratives about…”
Section: Current Studymentioning
confidence: 99%